Efeito do caulim sobre a morfologia, anatomia e trocas gasosas do cafeeiro (Coffea arabica L.) - Costa, Bruna Penha (2023)
Coffee is a species sensitive to abiotic stresses that can cause morphological and anatomical changes, in addition to interfering with its photosynthetic rate as a reflection of its influence on gas exchange. In the search for solutions to mitigate these stresses, studies on products with antiperspirant action have been intensified in recent years, such as kaolin, a modified clay that has reflective properties. The objective of this work was to evaluate the effects of the application of kaolin doses in different colors with and without the addition of adjuvant on the growth variables as well as on the leaf anatomy and gas exchange of arabica coffee cultivar IPR 100. The experiment was carried out at the Experimental Station of Horticulture and Biological Control Professor Mário César Lopes in the municipality Marechal Cândido Rondon - PR, exposed to field conditions during the period from November 2, 2020 to May 8, 2021. The experimental design was randomized blocks, with three replications, in incomplete factorial scheme with additional treatment, totaling 11 treatments and 33 plots. The first factor was constituted by three doses of kaolin (20, 40 and 60 g), the second factor by two colors of kaolin (white and cream), the third factor by the absence or presence of adjuvant and the additional treatment. The plot consisted of four seedlings of the IPR 100 cultivar. The morphological variables evaluated were: plant height (PH), stem diameter (SØ), number of plagiotropic branches (NPB), leaf area index (LAI), material leaf dry matter (MFM), stem dry matter (SM), root system dry matter (RSM), shoot dry matter (SM) and total dry matter (TM). Anatomical variables: adaxial (AD) and abaxial (AB) cuticle thickness, adaxial (CAD) and abaxial (CAB) epidermis thickness, palisade (EP) and spongy (ES) parenchyma thickness, xylem vessel thickness (XI) and phloem (PH) and leaf blade (LE), as well as the number of stomata (NS) per mm2 , polar (ØP) and equatorial (ØEQ) diameter of the stomata. And the gas exchange variables: net CO2 assimilation (A), stomatal conductance (gs), internal CO2 concentration in the substomatal chamber (Ci), transpiration rate (Trmmol), and the efficient use of WUE water. Dose 40 of white kaolin with adjuvant provided greater effect on growth variables. The 20 g dose of cream kaolin with adjuvant influenced the increase in the production of the cuticular layer in the coffee tree. The thickness of the cuticle and palisade parenchyma was reduced when 40 g of white kaolin was applied without adjuvant, however this same dose favored the increase in the diameter of the xylem vessel the increase in the number of stomata. Photosynthesis was positively influenced by the application of kaolin, with emphasis on the treatments 20 and 40 g white kaolin with adjuvant and 20 and 40 g cream kaolin with adjuvant.